2007
DOI: 10.1165/rcmb.2007-0012oc
|View full text |Cite
|
Sign up to set email alerts
|

Fluvastatin Inhibits Hypoxic Proliferation and p38 MAPK Activity in Pulmonary Artery Fibroblasts

Abstract: The earliest structural change in hypoxia-induced pulmonary hypertension is increased proliferation of adventitial fibroblasts. This fibroproliferative response occurs in acute and chronic hypoxic models, is dependent on p38 mitogen-activated protein (MAP) kinase activation, is selective for the pulmonary circulation, and would seem an important therapeutic target. Simvastatin attenuates pulmonary vascular remodeling in animal models, but additional information regarding mechanisms of action, differential anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
21
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 50 publications
2
21
0
Order By: Relevance
“…These GTPases regulate many cellular functions and couple membrane growth factor receptors to intracellular pathways that affect cell proliferation [6,7,9]. RhoA and its downstream mediator Rho-kinase have become an attractive target for the treatment of PAH [2,7].…”
mentioning
confidence: 99%
“…These GTPases regulate many cellular functions and couple membrane growth factor receptors to intracellular pathways that affect cell proliferation [6,7,9]. RhoA and its downstream mediator Rho-kinase have become an attractive target for the treatment of PAH [2,7].…”
mentioning
confidence: 99%
“…Different statins inhibited adventitial fibroblast proliferation, and reduced p38 activation. The statin-mediated effect can be mimicked by inhibition of GGTase-1 or Rac1 (Carlin et al, 2007). Thus, as they did for VSMCs, statins inhibited proliferation via inhibition of GGTase-1 activity, probably preventing Rac1 activation.…”
Section: Fibroblastsmentioning
confidence: 76%
“…Enhanced proliferation of adventitial fibroblasts is detrimental, such as in hypoxiainduced pulmonary hypertension. Excessive fibroblast proliferation under these conditions was caused by a Rac1/p38 signaling cascade (Carlin et al, 2007). Different statins inhibited adventitial fibroblast proliferation, and reduced p38 activation.…”
Section: Fibroblastsmentioning
confidence: 95%
“…In contrast, Satoh et al [28] reported that pravastatin administration did not significantly reduce right ventricular systolic pressure and right ventricular/left ventricular and interventricular septal weight in rats, whereas both simvastatin and atorvastatin did. Fluvastatin was shown to reduce right ventricular pressure, right ventricular hypertrophy and muscularization of pulmonary artery, inhibit pulmonary adventitial fibroblast proliferation and restore endothelial dysfunction in rat models of hypoxiainduced PAH [30,48]. Similarly, rosuvastatin significantly ameliorated right ventricular hypertrophy, vascular remodelling and endothelial dysfunction, reduced right ventricular systolic pressure and suppressed peroxynitrite formation in rats with PAH [49,50].…”
Section: Experimental Animal Modelsmentioning
confidence: 95%
“…Among them, simvastatin is the most well studied and was shown to attenuate PAH in both male and female rats by exerting several beneficial effects: reductions in mean PAP [23][24][25][26][27], right ventricular systolic pressure [28], right ventricular/left ventricular and interventricular septal weight [23,24,27,28] and right ventricular hypertrophy [25,26,29]; amelioration of pulmonary vascular remodelling (i.e. neointimal formation [29], muscularization and medial thickening [23,24,27]) via reduced proliferation and increased apoptosis of smooth muscle cells and endothelial cells [25,29], as well as inhibition of adventitial fibroblast proliferation [30]; improvement of oxidative status via upregulation of endothelial nitric oxide synthase (eNOS) [29,31,32] and reduction in reactive oxygen species production [26]; and inhibition of peribronchial and perivascular inflammation [32] via suppression of inflammatory genes expression (i.e. fos, jun and tumour necrosis factoralpha) [31].…”
Section: Experimental Animal Modelsmentioning
confidence: 99%